PHAGE FORMATION IN STAPHYLOCOCCUS MUSCAE CULTURES : V. FURTHER OBSERVATIONS ON THE RELATIONSHIP BETWEEN VIRUS RELEASE AND CELLULAR LYSIS - Price, Winston H. (The Rockefeller University Press, 1949)
1. In the synthetic medium of Fildes contaming hydrolyzed casein virus release is not correlated with observable cellular lysis under conditions of a very low multiple infection. 2. In cells with a high multiple infection, lysis occurs much sooner than in cells with a low multiple infection and virus release is correlated with cellular lysis. The experiments indicate that it is the virus particle itself which accelerates lysis under these conditions. 3. A non-dialyzable fraction has been isolated from yeast, the addition of which results in cellular lysis occurring at a sooner than usual interval and being correlated with virus release in cells having a very low multiple infection. 4. By varying the concentration of the yeast fraction, it is possible to lyse the cells at varying times under conditions of a low multiple infection.